Effectiveness and biocompatibility of a novel Schlemm’s canal microstent for glaucoma management - Huang, Manman; Zhang, Yu; Chen, Zhao; Liu, Changgeng; Wang, Jiaojiao; Feng, Xiaomei; Cheng, Wenjun; Wu, Qianyu; Wang, Yingfan; Liu, Qian (Scientific reports, 2024)
To evaluate the effectiveness and biocompatibility of Wistend, a novel Schlemm’s canal (SC) microstent made of Nitinol designed to improve aqueous humor outflow. New Zealand white (NZW) rabbits were divided into blank, sham-operated and Wistend groups. ICare ® Tonovet Plus ® , swept-source optical coherence tomography (SS-OCT), slit lamp biomicroscopy, retinal camera and scanning electron microscopy (SEM) were used for preoperative and postoperative observations. Hematoxylin and Eosin (H&E) tissue staining was adopted for biocompatibility. A significant difference in intraocular pressure (IOP) between the Wistend group and the control groups was observed during the six-month follow-up. SS-OCT identified arc line internal reflections within the SC in the anterior chamber angle. Conjunctival congestion and edema gradually diminished in the early stages. No corneal vascularization, no anterior chamber inflammatory response and no significant tissue reactions were noted in any groups. SEM showed the Wistend’s windows and orifices remained clear, encircled by minimal incidental ocular tissue and free from blockage. Histopathological examination revealed no discernible differences between the Wistend-implanted and sham-operated eyes. These in vivo studies demonstrate the effectiveness and biocompatibility of the microstent. Our findings suggest a promising potential for Wistend in significantly reducing IOP and effectively facilitating the outflow of aqueous humor.